2009
DOI: 10.1161/strokeaha.108.522557
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Abnormal Glucose Metabolism and Insulin Resistance Among Subtypes of Ischemic Stroke in Japanese Patients

Abstract: Background and Purpose-The purpose was to assess the prevalence of disorders of glucose metabolism and insulin resistance in Japanese ischemic stroke patients with no history of diabetes by performing 75-gram oral glucose tolerance test (OGTT). Methods-We recruited 427 ischemic stroke patients (atherothrombotic infarction, nϭ220; lacunar infarction, nϭ125; cardioembolic infarction, nϭ82). OGTT was used to evaluate disorders of glucose metabolism in stroke patients without previously known diabetes (nϭ113). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 29 publications
1
38
1
Order By: Relevance
“…The Funagata study showed that not only diabetes but also IGT was an independent risk factor for cardiovascular disease, whereas the IFG level was not a risk factor 13) . A high incidence of these types of prediabetic conditions among symptomatic stroke patients has been reported from both Asian and Western populations [14][15][16][17] . These prediabetic conditions were also correlated with a poor outcome after stroke 7,18) and increased the risk of reccurence 19) .…”
Section: Study Populationmentioning
confidence: 99%
“…The Funagata study showed that not only diabetes but also IGT was an independent risk factor for cardiovascular disease, whereas the IFG level was not a risk factor 13) . A high incidence of these types of prediabetic conditions among symptomatic stroke patients has been reported from both Asian and Western populations [14][15][16][17] . These prediabetic conditions were also correlated with a poor outcome after stroke 7,18) and increased the risk of reccurence 19) .…”
Section: Study Populationmentioning
confidence: 99%
“…Several studies from Europe and Japan in which OGTT was performed supplied either no diagnosis of IFG or small sample sizes. 13,24 Data on the prevalence of IFG and IGT among patients with intracerebral hemorrhage or SAH remained scarce. Our results indicate high prevalence of IGT and newly diagnosed DM in patients with intracerebral hemorrhage and SAH, which suggested that the identification of abnormal glucose regulation should be emphasized in the patients not only with ischemic stroke but also with intracerebral hemorrhage and SAH, and OGTT should be performed in all the stroke patients without history of diabetes after acute stage of stroke.…”
Section: Jia Et Al Abnormal Glucose After Stroke 653mentioning
confidence: 99%
“…A study from Japan with a small sample of 113 patients undergoing OGTT indicated that the prevalence of diabetes, only IGT, and only IFG among patients with ischemic stroke were 24.8%, 33.6%, and 3.5%, respectively, with the highest prevalence of IGT in the atherothrombotic infarction group. 13 In China, data on the prevalence of IFG or IGT among patients with stroke were scarce.…”
mentioning
confidence: 99%
“…Interestingly, nondiabetic ischemic stroke patients have an increased risk of mortality if their blood glucose levels are > 6.1 mM at early time points following the acute phase of ischemic stroke onset (17). In addition, the prevalence of abnormal glucose metabolism after the acute phase of ischemic stroke in 427 Japanese patients without a history of diabetes was 62.8% (18). Of them, a quarter of these patients had newly diagnosed diabetes (24.8%) and the rest of the patients had either impaired glucose tolerance or impaired fasting blood glucose (FBG) (18).…”
Section: Changes In Glucose Metabolism After Ischemic Stroke In Clinimentioning
confidence: 99%
“…In addition, the prevalence of abnormal glucose metabolism after the acute phase of ischemic stroke in 427 Japanese patients without a history of diabetes was 62.8% (18). Of them, a quarter of these patients had newly diagnosed diabetes (24.8%) and the rest of the patients had either impaired glucose tolerance or impaired fasting blood glucose (FBG) (18). Furthermore, in a recent study, Rosso et al reported that infarct growth was greater in patients with high blood glucose levels than in patients with low blood glucose levels after ischemic stroke (19).…”
Section: Changes In Glucose Metabolism After Ischemic Stroke In Clinimentioning
confidence: 99%